Impact of Geriatric Pharmacy Specialist Interventions to Reduce Potentially Inappropriate Medication Among Hospitalized Elderly Patients at Medical Wards: A Prospective Quasi-Experimental Study - Wajanakorn Chivapricha; Varalak Srinonprasert; Thanarat Suansanae (Drugs - Real World Outcomes, 2020)
Abstract Background Elderly patients are at greater risk of receiving potentially inappropriate medications (PIMs) and developing adverse drug events. Identification and correction of PIMs is essential to maximize medication safety. Objective To determine the prevalence of PIMs on admission in Thai elderly patients admitted to a medical ward and to compare changes of PIMs on discharge, following comprehensive care by a ward pharmacist with or without a geriatric pharmacy specialist. Patients and method A prospective, quasi-experimental study was performed at a tertiary university hospital in Bangkok, Thailand. Patients aged ≥ 60 years who were admitted to the medical ward were recruited and allocated to one of two groups: intervention (IG) and control (CG). The CG received pharmaceutical care from the ward pharmacist. The IG received pharmaceutical care from the geriatric pharmacy specialist along with the ward pharmacist. The 2012 Beers criteria were used to identify PIMs on admission, during hospitalization, and on discharge. Results Prevalence of PIMs on admission was 43.3% (N = 187). On discharge, prevalence of PIMs in the IG decreased significantly compared to that on admission (21.3% and 43.3%, p < 0.05) and was significantly lower than in the CG (21.3% and 40.9%, p = 0.036). Moreover, the percentage of patients without PIMs on discharge in the IG was significantly higher than in the CG (78.7% and 59.1%, p < 0.0001). Conclusion Use of PIMs was common among hospitalized elderly patients on admission. Pharmaceutical care provided by a geriatric pharmacy specialist in conjunction with a ward pharmacist significantly reduced the prevalence of PIMs on discharge compared with on admission.